2015
DOI: 10.1016/j.stemcr.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

A Non-invasive Platform for Functional Characterization of Stem-Cell-Derived Cardiomyocytes with Applications in Cardiotoxicity Testing

Abstract: SummaryWe present a non-invasive method to characterize the function of pluripotent stem-cell-derived cardiomyocytes based on video microscopy and image analysis. The platform, called Pulse, generates automated measurements of beating frequency, beat duration, amplitude, and beat-to-beat variation based on motion analysis of phase-contrast images captured at a fast frame rate. Using Pulse, we demonstrate recapitulation of drug effects in stem-cell-derived cardiomyocytes without the use of exogenous labels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 24 publications
2
94
0
1
Order By: Relevance
“…For example, Gilchrist et al (79) performed high-content MEA recordings at 0.5, 1, 2, and 4 h post exposure to compounds with known proarrhythmic properties (e.g., verapamil, ranolazine, flecainide, amiodarone, ouabain, cisapride, and terfenadine) and found that cardiotoxicity could be recapitulated in vitro using hiPSC-CMs. Similar data were presented using video-edge contractility analysis by Maddah et al (174).…”
Section: Generation and Characterization Of Hipsc-cms At A High-thsupporting
confidence: 70%
“…For example, Gilchrist et al (79) performed high-content MEA recordings at 0.5, 1, 2, and 4 h post exposure to compounds with known proarrhythmic properties (e.g., verapamil, ranolazine, flecainide, amiodarone, ouabain, cisapride, and terfenadine) and found that cardiotoxicity could be recapitulated in vitro using hiPSC-CMs. Similar data were presented using video-edge contractility analysis by Maddah et al (174).…”
Section: Generation and Characterization Of Hipsc-cms At A High-thsupporting
confidence: 70%
“…Proteasome inhibitors are an important class of compounds recently developed for cancer therapy, although treatment can be complicated by cardiac toxicity, which has been observed in animals and humans (31,32). To measure the effects of proteasome inhibitors on iPS-CM contractile motion, we used an automated video microscopy system (33). With this BAG3 is required to prevent severe cardiotoxicity from the proteasome inhibitor bortezomib.…”
Section: Resultsmentioning
confidence: 99%
“…Video microscopy-based motion field imaging analysis is able to characterize motion-derived contractile properties of cardiomyocytes (Ahola et al, 2014;Hayakawa et al, 2014;Maddah et al, 2015) in a non-invasive manner. Motion field imaging has been demonstrated to detect acute (<1 h) druginduced effects of cardiac ion channel drugs in hiPS-CMs (Hayakawa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%